Scrutiny of a very young, metal-poor star-forming Lyα emitter at z ≈ 3.7. Issue 4 (9th November 2022) - Iani, E; Zanella, A; Vernet, J; Richard, J; Gronke, M; Arrigoni-Battaia, F; Bolamperti, A; Caputi, K I; Humphrey, A; Rodighiero, G; Rinaldi, P; Vanzella, E
ABSTRACT: The origin of the Lyman α (Lyα) emission in galaxies is a long-standing issue: despite several processes known to originate this line (e.g. active galactic nucleus, star formation, cold accretion, shock heating), it is difficult to discriminate among these phenomena based on observations. Recent studies have suggested that the comparison of the ultraviolet (UV) and optical properties of these sources could solve the riddle. For this reason, we investigate the rest-frame UV and optical properties of Abell 2895b, a strongly lensed Lyα emitter at redshift z ∼ 3.7. From this study, we find that our target is a compact ( r n ∼ 1.2 pkpc) star-forming (star formation rate ≃11 M⊙ yr −1 ) galaxy having a young stellar population. Interestingly, we measure a high ratio of the Hβ and the UV continuum monochromatic luminosities ( L (Hβ)/ L (UV) ≃ 100). Based on tracks of theoretical stellar models (starburst99 and bpass ), we can only partially explain this result by assuming a recent (≲10 Myr), bursty episode of star formation and considering models characterized by binary stars, a top-heavy initial mass function and subsolar metallicities ( Z ≲ 0.01 Z⊙ ). These assumptions also explain the observed low (C/O) abundance of our target (≃0.23(C/O)⊙ ). By comparing the UV and optical data sets, we find that the Lyα and UV continuum are more extended (×2) than the Balmer lines, and that the peak of the Lyα is offset (≃0.6 pkpc). The multiwavelength results of our analysis suggest that the observed Lyα emission originates from a recent star formation burst, likely taking place in an off-centre clump.